PENGARUH PEMBELAJARAN MATEMATIKA BERBASIS AKIDAH AKHLAK TERHADAP SIKAP MODERASI BERAGAMA SISWA DI MTS. AL-KHAIRIYAH TEMPUREJO JEMBER - Moh. Al-Faiz; Jasuli Jasuli; Moh. Qurtubi; Ida Andriyani (FAJAR Jurnal Pendidikan Islam, 2024)
This study aims to examine the influence of faith and morality-based mathematics instruction on students' religious moderation attitudes at MTs. Al-Khairiyah Tempurejo Jember. A quasi-experimental method was employed with two groups: an experimental group that received mathematics instruction integrated with faith and moral values, and a control group that received conventional mathematics instruction. Data analysis utilized a t-test to assess significant differences between the two groups, alongside descriptive analysis to illustrate the profile of students' religious moderation attitudes. The results indicate that integrating faith and moral values into mathematics education enhances students' religious moderation, tolerance, and empathy. Additionally, this approach strengthens students' academic performance. The experimental group showed a more significant improvement compared to the control group. Thus, integrating faith and moral education into mathematics lessons is considered effective in shaping students' moderate and ethical character.